Dynamic Concept Maps for eTextbook Glossaries: Design and Evaluation - Elgendi, Ehsan; Shaffer, Clifford A. (Frontiers in Computer Science, 2020)
Glossaries play a major role in enhancing students’ comprehension of core concepts. Glossary terms have complex interrelationship that cannot be fully illustrated by standard approaches such as including all terms in a linear, alphabetized list. To overcome this limitation, we introduce an interactive design for glossary terms within the OpenDSA interactive eTextbook system using concept maps. Glossary terms are visualized as nodes in graphs and their relationships are described on the edges. A concept map associated with the selected term is generated on demand. We evaluate the effectiveness of our design by comparing student use of our concept-map based glossary to the traditional alphabetized list. We used exercises that target the comprehension of the glossary terms to make students familiar with the concept maps.